Nickel-catalyzed copolymerization of carbon dioxide with internal epoxides by di-nuclear bis(benzotriazole iminophenolate) complexes. (November 2019) - Li, Ming-Han; Liu, Guan-Lin; Su, Yu-Chia; Ko, Bao-Tsan
Graphical abstract: New well-characterized di-nuclear nickel bis(benzotriazole iminophenolate) complexes bearing homo- or mixed-monoanionic coligands were synthesized for CO2 -epoxides copolymerization. Di-Ni chloride 3 was demonstrated to efficiently copolymerize CO2 and CHO in a controllable character, producing highly alternating PCHCs with good activities and high selectivities. Highlights: Well-defined dinuclear Ni catalysts bearing BiIBTP ligands were synthesized. Catalysis for Ni-catalyzed copolymerization of CO2 with epoxides was studied. Di-Ni 1 could efficiently catalyze CO2 -copolymerization of CHO, CPO or VCHO. 3 is an effective catalyst for CO2 /CHO copolymerization with a high TOF. Abstract: We report the synthesis of structurally well-characterized di-nuclear nickel bis(benzotriazole iminophenolate) (BiIBTP) complexes containing diverse mono- or bi-dentate monoanionic coligands for the utilization of copolymerization of carbon dioxide (CO2 ) with internal epoxides. The molecular structures of complexes 1 –3 can be ascribed to bimetallic nickel(II) species containing a hexadentate BiIBTP main ligand and two homo-coligands of pentafluorobenzoate, pentafluorophenolate or chloride, whereas 4 and 5 are BiIBTP-ligated di-nickel chloride analogues mixed with carboxylate coligands. Di-nickel complexes 1 and 3 supported by O2 CC6 F5 and Cl coligands were demonstrated to be efficient catalysts for alternating copolymerization of CO2 with cyclohexene oxide (CHO) to afford CO2 -based poly(cyclohexene carbonate)s (PCHCs) with >99% carbonate repeated units. Particularly, di-Ni di-chloride complex 3 was capable of giving high activity with a turnover frequency of 688 h −1 for such copolymerization under the optimal conditions. Interestingly, di-Ni catalyst 1 enables us to produce the low molecular weight di-hydroxyl end-capped PCHCs with unimodal molecular weight distributions while commercially available CHO without further purification was used as the epoxide monomer. In addition to CO2 -CHO copolymerization, bimetallic complex 1 was also found to effectively copolymerize CO2 with cyclopentene oxide, generating highly alternating poly(cyclopentene carbonate)s with molecular weights in a broad range. Kinetic studies of CO2 /CHO copolymerization catalyzed by 1 were investigated using 1 H NMR spectroscopy and revealed the first-order dependence for both catalyst 1 and CHO concentrations.